2019
DOI: 10.1016/j.molcel.2019.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of DNA End Sensing and Processing by the Mre11-Rad50 Complex

Abstract: Highlights d cryo-EM structure of EcMre11-Rad50 bound to a DNA break d Mre11 dimer binds the DNA end at the side of Rad50 d Mre11 and Rad50 assemble a transient DNA cutting channel d The coiled coils form a rod-shaped DNA gate and clamp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 77 publications
8
117
0
Order By: Relevance
“…Li et al showed the physiological of peroxisome proliferator-activated receptor γ(PPARγ) and DNA damage response (DDR) by using pulmonary arterial hypertension (PAH) as a model that impaired PPARγ signalling pathway related to endothelial cell dysfunction and disrupted PPARγ-UBR5 (MRE11-RAD50-NBS1) interaction, heightened ATM interactor (ATMIN) expression and DNA lesions. Therefore, PPARγ-DDR dysfunction may explain the genomic instability and loss of endothelial homeostasis in PAH [ 22 ]. According to a study conducted by Qinlan Wang, Smc4, a core subunit of condensin, to potentially promote an inflammatory innate immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al showed the physiological of peroxisome proliferator-activated receptor γ(PPARγ) and DNA damage response (DDR) by using pulmonary arterial hypertension (PAH) as a model that impaired PPARγ signalling pathway related to endothelial cell dysfunction and disrupted PPARγ-UBR5 (MRE11-RAD50-NBS1) interaction, heightened ATM interactor (ATMIN) expression and DNA lesions. Therefore, PPARγ-DDR dysfunction may explain the genomic instability and loss of endothelial homeostasis in PAH [ 22 ]. According to a study conducted by Qinlan Wang, Smc4, a core subunit of condensin, to potentially promote an inflammatory innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Qinlan Wang, Smc4, a core subunit of condensin, to potentially promote an inflammatory innate immune response. They suggested that knockdown of Smc4 inhibited Toll-like receptor-mediated production of proinflammatory cytokines such as IL-6, TNF-α in macrophages [ 22 , 23 ]. HMGB1-TLR4 signaling axis has been shown to stimulate neutrophil NADPH oxidase (NOX2) in both neutrophils and lung microvascular endothelial cells, and NOX2 has played essential roles in the pathogenesis of PH.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed in a previous study that distal intragenic suppressors within the coiled coil domain influence the disposition of the globular domain via the changes in the path of the coiled coils [8]. This proposal is supported by a recent structural study of the E. coli ortholog of the Mre11 complex, SbcCD [45]. The observation that the ATPase function specified in the globular domain is influenced by a coiled coil mutation lends further support to this presumptive mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…Crystal structures of ATP analogue-bound Mre11-Rad50 in complex with double-strand DNA (dsDNA) and recent cryoEM structure of the E. coli Mre11-Rad50 homolog in complex with DNA reveal an ATP-dependent clamp-like mechanism ( Fig. 2d) [27][28][29][30]. Upon ATP binding, the two Rad50 head domains close up to facilitate the binding of DNA.…”
Section: Architecture Of the Mrn Complex: The Initiator Of The Dsb Rementioning
confidence: 99%
“…Upon ATP binding, the two Rad50 head domains close up to facilitate the binding of DNA. Upon ATP hydrolyses, the Rad50 dimeric head domains dissociate, exposing the nuclease site of Mre11 to carry out DNA resection [28][29][30][31][32]. However, how the ATPdependent open-close transition is regulated upon DSB recognition, repair initiation and downstream signalling transduction is still not well understood.…”
Section: Architecture Of the Mrn Complex: The Initiator Of The Dsb Rementioning
confidence: 99%